1999
DOI: 10.1002/(sici)1522-2683(19990701)20:10<2039::aid-elps2039>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

On the mechanism of background silver staining during sodium dodecyl sulphate-polyacrylamide gel electrophoresis

Abstract: A novel experimental procedure to study the factors that contribute to background silver staining in sodium dodecyl sulphate‐polyacrylamide gel electrophoresis (SDS‐PAGE) is described. A mechanism is proposed for background silver staining, which was found to result primarily from the redox initiator system using ammonium persulphate (APS) and an amine such as N,N,N′,N′‐tetramethylethylenediamine (TEMED).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…We have previously reported that an increased potential functionality of a cross-linker promotes networks with bigger pores. 32 This is also observed by SEM experiments (Figure 3, comparing Bis to 1). The phase separation experienced by 1 cross-linked gels 31 and the added functionality effect on the heterogeneity of the network 32 may contribute to the reduced reactivity effect observed between the two gel networks with 1 and 2.…”
Section: Discussionsupporting
confidence: 77%
“…We have previously reported that an increased potential functionality of a cross-linker promotes networks with bigger pores. 32 This is also observed by SEM experiments (Figure 3, comparing Bis to 1). The phase separation experienced by 1 cross-linked gels 31 and the added functionality effect on the heterogeneity of the network 32 may contribute to the reduced reactivity effect observed between the two gel networks with 1 and 2.…”
Section: Discussionsupporting
confidence: 77%
“…Meanwhile, the higher characteristic signal intensities of the DMPO-OH adduct and DMPO-SO 4 adduct in KPS–PEI NPs + DMPO are higher than that of K 2 S 2 O 8 + DMPO, suggesting that more SO 4 · – and OH · are trapped in KPS–PEI NPs. Inspired by the use of N , N , N ′, N ′-tetramethylethylenediamine to catalyze the generation of free radicals from persulfate in polyacrylamide gel electrophoresis, , we proposed the reaction mechanism of PEI NPs and S 2 O 8 2– (Scheme S4). KPS–PEI NPs, rich in ethylenediamine structural units, could effectively promote the generation of SO 4 · – not only through electrocatalysis (eq ) but also via chemical reactions (eq ), so it is an excellent coreaction accelerator.…”
Section: Resultsmentioning
confidence: 99%
“…To synthesize hydrogels of pNIPAM-chitosan copolymer, different components, including chitosan, NIPAM and MBA were dissolved in 1% (w/v) acetic acid. Addition of the radical initiator, APS, was followed by incorporation of TEMED, resulting in decomposition of APS through a redox reaction [33], making radicals available for the initiation of the polymerization. Following addition of TEMED, and due to the presence of MBA, the hydrogel backbone rapidly started to form, as demonstrated in Scheme 1.…”
Section: Sol-gel Synthesis Of Pnipam-chitosan Copolymermentioning
confidence: 99%